Does Piroxicam really protect ischemic neurons and influence neuronal firing in cerebral ischemia? An exploration towards therapeutics - Bhattacharya P.; Pandey A.K.; Paul S.; Patnaik R. (My University, 2025)
Cerebral ischemia is still one of the most confusing and enigmatic neurological disorders with least understood injuries. The EEG measures have been traditionally used to detect residual neural dysfunctions after cerebral ischemia although having several shortcomings, yielding controversial and inconsistent results. It is feasible to hypothesize that advanced EEG research can overcome these shortcomings and provide more clear information regarding the long lasting neural impairment in the subjects suffered from brain stroke. To our understanding, EEG power spectrum density measures can significantly contribute towards intervening drug administered diseased model and give us correct status of neuronal firing after an insult. On the basis of our findings we hypothesize that Piroxicam, a non-steroidal anti-inflammatory drug (NSAID) can protect neurons and improves neuronal firing after ischemia/reperfusion injury in animal model of focal cerebral ischemia. This is the first ever finding which advocates the role of Piroxicam, a NSAID in neuronal firing apart from its other neuroprotective roles. Thus, we consider the possibility of modulation of neuronal firing as a therapeutic strategy to help prevent neuronal dysfunctions in cerebral ischemia. © 2013 Elsevier Ltd.